The never-ending role of nurses during the COVID-19 era - Subrata, Sumarno Adi (Journal of Holistic Nursing Science, 2021)
As we have seen during the times, the prevalence of COVID-19 is going to be increased worldwide. A total of 183,560,151 confirmed cases of COVID-19 including 3,978,581 deaths was reported. This data surprised all healthcare professionals such as nurses working in the hospital and primary care in the community. As the consequence, a call for massive intervention is urgently needed particularly in Indonesia. This can be achieved by optimizing health promotion in the community, opening research grants for nurses, recruiting nursing volunteers, and coordinating with the government along with stakeholders in the healthcare services. In addition to that, a scientific publication focusing on innovative care is also essential to support the ongoing health policy. We finally hope, this pandemic will end soon. However, we must be ready to live with COVID-19 as they will always stay with us, forever.